Injection preparation filtration and health concerns among indigenous people who inject methamphetamine - Anastario, Michael; Suarez, Andrea; Williamson, Olivia; Firemoon, Paula; Roberts, Elizabeth F. S.; Barber, Jarrett (Frontiers in Public Health, 2024)
Introduction Injecting methamphetamine poses significant health risks, but little is known about how methamphetamine injectors filter their injection preparations and experience related health concerns. Methods A chain-referral sample of Indigenous people who inject methamphetamine (n = 30) was recruited and semistructured interviews were conducted to collect information on filtration practices and health concerns. Results Filtration of the injection preparation was described by 53% of injectors. Elevated levels of concern for kidney disease, cancer and heart disease were observed among those who filtered their preparations (ranging from 50 to 56.3%). Concern about liver disease was the most frequent concern among those who filtered their preparations (62.5%) and was elevated in comparison to those who did not use filters (7.1%). Grouped logistic regression revealed a positive association between filtration of the injection preparation and overall health concerns expressed by injectors, after adjusting for gender and age. The marginal posterior distribution of the adjusted odds ratio for filtration of the injection preparation had a posterior median = 35.7, and 95% HPD interval = (5.1, 512.4). Discussion Results illustrate a positive relationship between filtration of the injection preparation and health concerns among Indigenous people who inject methamphetamine. This likely reflects the use of filtration to reduce harms, and further research is needed to understand the full scope of prevention that may be associated with filtration of methamphetamine injection preparations.